6, 7, 8, and 9. just plug the X into the equation
Given the function f(x) = (x + 1)^2 - 3, we recognize that because of the x^2 factor we have a parabola that opens up. Its vertex is (-1, -3), which I have swiped from the given equation. The axis of symm is x= -1.
Answer:
To inches?
Step-by-step explanation:
75 cm = is about like 30 inches
Answer:
I will show all the steps to lead to the solution.
1) 10b = 5 (√c + 2) <---- starting equation
2) divide by 5 => 2 b = √c + 2
3) subtract 2 => 2b - 2 = √c
4) raise to the power 2 => (2b - 2)^2 = c, which is the expression given.
Now these are two equivalent forms:
1) extract 2 from the parentheses: c = 4 (b -1)^2
2) expand the parentheses: c = 4b^2 - 8b + 4)
Step-by-step explanation:
Choice D
Answer:
The answer is 91/10
Step-by-step explanation:
hope this helps
Solutions:
2 3/5÷2/7
13/5÷2/7
13/5×7/2
=13×7=91
=5×2=10
That's why the answer is 91/10